The Effect Of Accounting Understanding, Tax Incentives, And Tax Socialization On Pmk 86/2020 On Msme Taxpayer Compliance Affected By The Pandemic - Stephanie Stephanie (Jurnal Indonesia Sosial Teknologi, 2022)
The world economy has experienced shocks in recent years due to the arrival of the Covid-19 Virus. This causes the world economy to drop drastically and has an impact on tax stability. This study aims to determine the effect of understanding accounting, tax incentives, and tax socialization about PMK 86/2020 on MSME taxpayer compliance affected by the 2019 corona virus disease pandemic in Tangerang City. The authors obtained this research through distributing questionnaires through social media such as Facebook, Whatsapp, and Instagram. The test was carried out using a purposive examination technique on 100 respondents. Handled information checks using the SPSS 26 program with descriptive measurable tests, information quality tests, exemplary presumption tests, various direct relapse investigation tests, and speculation tests. The results of this review indicate that the understanding of bookkeeping has a significant effect on the consistency of MSME taxpayers, the cost drive has no effect on the consistency of MSME taxpayers, and expenditure socialization has a significant effect on the consistency of MSME taxpayers.